Detection of antibodies to Toxoplasma gondii in wild animals in Brazil - Silva, Rodrigo Costa Da; Machado, Gustavo Puglia; Cruvinel, Tatiane Morosini De Andrade; Cruvinel, Ciro Alexandre; Langoni, Hélio [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2014)
Background Toxoplasmosis is a worldwide zoonosis caused by an obligate intracellular protozoan parasite, Toxoplasma gondii, that affects all warm-blooded animals, including wild animals. The increased number of cases of parasitic infections is mainly due to the destruction of environmental conservation areas, which is driving wild animals out of their habitats and towards urban areas. In this study, the occurrence of T. gondii infection was investigated by the modified agglutination test (MAT) in 26 different species of run over and injured wild animals that were treated at a Brazilian university veterinary hospital, from June 2007 to August 2008. Findings Of the studied animals, six (23.1%; CI95% 11.1-42.2%) had T. gondii antibodies, with titers equal to 10 (4; 66.7%) and 40 (2; 33.3%). The species Pseudalopex vetulus, Cerdocyon thous, Hydrochoerus hydrochaeris and Tapyrus terrestris had titers of 10, while Alouatta caraya and Puma concolor had titers of 40. There was no significant association regarding age, gender or purpose of care (p > 0.05). Conclusions Carnivorous, herbivorous and omnivorous wild animals are potential sentinels of human toxoplasmosis, especially when wild felids are present, maintaining the environmental contamination.
Keywords: Toxoplasma gondii; Natural infection; Antibodies; Wild animals; MAT